Current Proceedings of Cerebral Palsy. Issue 3 (March 2015) - Fan, Hueng-Chuen; Ho, Li-Ing; Chi, Ching-Shiang; Cheng, Shin-Nan; Juan, Chun-Jung; Chiang, Kuo-Liang; Lin, Shinn-Zong; Harn, Horng-Jyh
Cerebral palsy (CP) is a complicated disease with varying causes and outcomes. It has created significant burden to both affected families and societies, not to mention the quality of life of the patients themselves. There is no cure for the disease; therefore, development of effective therapeutic strategies is in great demand. Recent advances in regenerative medicine suggest that the transplantation of stem cells, including embryonic stem cells, neural stem cells, bone marrow mesenchymal stem cells, induced pluripotent stem cells, umbilical cord blood cells, and human embryonic germ cells, focusing on the root of the problem, may provide the possibility of developing a complete cure in treating CP. However, safety is the first factor to be considered because some stem cells may cause tumorigenesis. Additionally, more preclinical and clinical studies are needed to determine the type of cells, route of delivery, cell dose, timing of transplantation, and combinatorial strategies to achieve an optimal outcome.